2021
DOI: 10.1111/ffe.13515
|View full text |Cite
|
Sign up to set email alerts
|

General quantification of fatigue damage with provision for microstructure: A review

Abstract: Recent developments in microstructure‐sensitive computational modeling and experimental verification have provided significant insight on how one can estimate fatigue damage and predict useful life. As a myriad of methods and approaches are available, it is important to understand how to properly utilize them in a unified and efficient framework for the quantification of damage in safety‐critical components such as jet engine fan blades, gas turbine disks, and airframe structural connections. To this end, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…where the value of constants a hkl , c hkl , A hkl0 , and B hkl , tabulated in Vlassak and Nix, 44 depend on v <100> , which is the Poisson ratio in the <100> direction. And the anisotropy ratio A can be solved for Equation (18):…”
Section: Crystal Plasticity Modeling and Parameter Calibrationmentioning
confidence: 99%
“…where the value of constants a hkl , c hkl , A hkl0 , and B hkl , tabulated in Vlassak and Nix, 44 depend on v <100> , which is the Poisson ratio in the <100> direction. And the anisotropy ratio A can be solved for Equation (18):…”
Section: Crystal Plasticity Modeling and Parameter Calibrationmentioning
confidence: 99%
“…In fact, the reliable assessment of the fatigue life of parts produced by new manufacturing technologies, such as AM, requires extensive experimental testing campaigns, and, since microstructural defects appear in large quantities, the role of microstructure has become increasingly important. 16 Additionally, the fatigue properties of SLMed parts highly depend on the surface roughness and mainly on the process-induced defects (pores and lack of fusion) commonly located mainly within 250 μm of the surface and tend to decrease to the interior of the component. 17 Hence, high fatigue resistance improvements can be obtained by machining external layers of the parts at a depth greater than the indicated and by removing subsurface defects 17 since this has proven to be an easy and reliable post-treatment process of stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some critical plane models can predict the fatigue crack directions, 6,7 and energy-based models include thermodynamical effects. [8][9][10][11] Castelluccio and McDowell, 12 Stopka and McDowell, 13 and Przybyla et al 14 showed that the Fatemi-Socie (FS) parameter could be used as the local driving force for fatigue crack formation and early growth in mesoscale simulations.…”
Section: Introductionmentioning
confidence: 99%